Nano-phytoremediation technologies for groundwater contaminates emerging research and opportunities - Chaudhary, Khushboo; Khan, Suphiya; Saraswat, Pankaj Kumar (IGI Global, 2020)
"This book explores phytoremediation and some experimental methods used in life science laboratories. It also examines various heavy metals and non-metals and their effect on remedial approaches"--